Influenza B Virus: Some Features of Clinical Findings and Etiotropic Treatment - O. V. Maltsev; I. S. Grishin; E. V. Peredelsky; N. I. Lvov; K. V. Zhdanov (Журнал инфектологии)
Since January 1997 till March 2009 492 patients with a confirmed diagnosis of influenza A virus and influenza B virus underwent work-up in Military Medical Academy. It is established that the clinical findings of influenza B virus are accurately different from the clinical findings of influenza A virus. Influenza B virus is characterized by more prolonged fever, lower incidence and duration of some respiratory syndromes and fewer sequelae. The influence of etiotropic drugs and early interferon inducers on influenza B virus course was studied. Neuraminidase inhibitors are the most effective antiviral therapy agent for influenza B virus. At the same time, there was a significant reduction in the duration of the common infectious intoxication syndrome and respiratory tract damage.